2008
DOI: 10.1073/pnas.0802789105
|View full text |Cite
|
Sign up to set email alerts
|

Lack of aldose 1-epimerase in Hypocrea jecorina (anamorph Trichoderma reesei ): A key to cellulase gene expression on lactose

Abstract: The heterodisaccharide lactose (1,4-O-␤-D-galactopyranosyl-Dglucose) induces cellulase formation in the ascomycete Hypocrea jecorina ‫؍(‬ Trichoderma reesei). Lactose assimilation is slow, and the assimilation of its ␤-D-galactose moiety depends mainly on the operation of a recently described reductive pathway and depends less on the Leloir pathway, which accepts only ␣-D-galactose. We therefore reasoned whether galactomutarotase [aldose 1-epimerase (AEP)] activity might limit lactose assimilation and thus inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Much of the research on cellulase induction by lactose has focused on the metabolism of lactose. 34,56,57) Despite observations that indicate that lactose is a stronger inducer than Dgalactose, 33) the importance of lactose permeases on cellulase formation has not attracted widespread attention. In this study, we identified two major facilitator superfamily sugar transporters involved in lactose uptake and cellulase induction by lactose in an industrial strain of T. reesei.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the research on cellulase induction by lactose has focused on the metabolism of lactose. 34,56,57) Despite observations that indicate that lactose is a stronger inducer than Dgalactose, 33) the importance of lactose permeases on cellulase formation has not attracted widespread attention. In this study, we identified two major facilitator superfamily sugar transporters involved in lactose uptake and cellulase induction by lactose in an industrial strain of T. reesei.…”
Section: Discussionmentioning
confidence: 99%
“…A plausible explanation for this is the use of lactose, the substrate of b-galactosidase, for induction of cellulase gene expression in commercial fermentations (Fekete et al, 2008). Corn stover contains little if any b-linked galactose.…”
Section: The Secretome Of T Reeseimentioning
confidence: 99%
“…It supports the glucose tolerant BGL production and it is utilized in the commercial production of the enzyme owing to economic considerations [10]. The mechanism of lactose induction, however, is not fully understood [11].…”
Section: Differential Expression Ofˇ-glucosidasesmentioning
confidence: 99%